Effect of nano-scale textures on cutting performance of WC/Co-based Ti55Al45N coated tools in dry cutting. (July 2015) - Zhang, Kedong; Deng, Jianxin; Meng, Rong; Gao, Peng; Yue, Hongzhi
Abstract: It is well known that topographical features on contact surfaces have a significant impact on friction and wear. Indeed, surfaces that entail a texture are being used to improve and/or control the performance of sliding surfaces. In this study, two kinds of novel WC/Co-based Ti55 Al45 N coated tools were developed utilizing femtosecond laser technology and cathode arc-evaporation technique: the first one, nano-scale surface texturing was produced on the rake face close to the main cutting edge of the WC/Co carbide tools, these textured tools were then deposited with Ti55 Al45 N hard-coatings; the second one, Ti55 Al45 N hard-coatings were deposited onto the carbide tools, nano-scale surface texturing was then produced on the coated tool surfaces. This paper details the effect of nano-scale textures and their processing sequence on cutting performance of WC/Co-based Ti55 Al45 N coated tools. Dry cutting tests were carried out on hardened steel with the firstly nano-scale textured and then Ti55 Al45 N coated tools (NCT), the firstly Ti55 Al45 N coated and then nano-scale textured tools (CNT), and the conventional coated tool (CCT). A reduction in cutting forces, cutting temperatures, friction coefficient at the tool–chip interface and tool wear that ensues from nano-scale textures is demonstrated, and the CNT tools are more effective compared with the NCT ones. In addition, the geometry of nano-scale textures has a profound effect, the coated tool with areal nano-scale textures shows better cutting performance compared to the one with partial nano-scale textures parallel to the main cutting edge. The possible effect mechanisms of nano-scale textures were discussed. Hence, it is expected that the results of this study can be applied to improve the performance and reduce the wear of coated tools in dry cutting. Highlights: We report two novel WC/Co cutting tools which are nano-textured and Ti55 Al45 N coated. Cutting force, cutting temperature, friction coefficient, and tool wear are measured. The effect of nano-texture varies with processing sequence of surface texturing. The mechanism responsible for improving performance by nano-texture is proposed.